The Effect of Economic Constraints on Direct Real Estate Market - Al-Qaisi, khaldoun Maddaallah (Universitas Prasetiya Mulya, 2021)
The objective of this research to investigate the interactions between the direct real estate markets with the financial stock market changes. To accomplish this objective data was collected of different official secondary sources. The collected data entered to SPSS and E-views for analysis. The results of this research showed that there is high interaction between the real estate market performance in Jordan and stock exchange market.Keywords: Direct real estate market, financial stock exchange market.Â Â https://doi.org/10.21632/irjbs.14.1.27-34